Implementasi Metode Hear Them Out, Empathize, Apologize dan Taking Proper Action and Follow Up (Head) Sebagai Pelayanan Prima Bisnis Perhotelan - Yusuf Ihza Mahendra; Dewi Harmin Sutanto (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2021)
The purpose of this study was to determine the effect of hotel service quality on customer satisfaction. This research is a type of library research (library research). Sources of data studied in this research are books, scientific articles from journals, papers, magazines, etc., which are relevant to this research and can answer the main problems. Meanwhile, the approach used in this research is philosophical. While the data collection technique used is documentation. The analysis method used is content analysis to direct the accuracy of the data under study. The findings of this study indicate that the quality of hotel services is very influential on customer satisfaction. If a hotel can provide complete services and products, the customers or hotel guests will be satisfied. Conversely, when hotel services and products are presented in a perfunctory and unprofessional manner, lack of management and good service techniques, there will be various complaints, complaints, and dissatisfaction from customers or hotel guests.